Namesake ebook A novel. - Young, Adrienne (World of the Narrows, 2021)
INSTANT NEW YORK TIMES BESTSELLER Following the Hello Sunshine Book Club pick Fable , New York Times bestselling author Adrienne Young returns with Namesake, a captivating conclusion to the duology, filled with action, emotion, and lyrical writing. Trader. Fighter. Survivor. With the Marigold ship free of her father, Fable and its crew were set to start over. That freedom is short-lived when she becomes a pawn in a notorious thug's scheme. In order to get to her intended destination she must help him to secure a partnership with Holland, a powerful gem trader who is more than she seems. As Fable descends deeper into a world of betrayal and deception, she learns that the secrets her mother took to her grave are now putting the people Fable cares about in danger. If Fable is going to save them then she must risk everything, including the boy she loves and the home she has finally found.